(3fUGH GdGMJSGHs - (3YeQ Hf eMeO Hf YhV GdTGej GdMfaj GdSfGej,J (B696 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdMSjH GdQbjH Ydi fhGdg EjeGfkG hGMJSGHkG CeG HYO abO LeY YHOg eSGFd GNJUJ HGdfSHI Edi MSH efUH GdMSHI s
(3BNQgG (B:s
(3hEPG GJJ GdeQGI GdbQjHI ddJYRjI aJfhM Ydi GdejJ gd jLhR ddeMJSH Cf jNQLgG ef HjJ ZjQg EPG de jNQLgG Cgdg GdLhGH fYe dGHf YeQ QVi (B[ (3Gddg Yfg (B] (3CNQL CNJ CHj HcQ QVi Gddg Yfg ef HjJg Mjf fGMJ ef UMM GdHNGQi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B63 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B317s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1953s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs